2007
DOI: 10.1093/humrep/dem353
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chromatin structure assay parameters measured after density gradient centrifugation are not predictive for the outcome of ART

Abstract: SCSA performed in semen prepared by DGC cannot predict the outcome of ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
2
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 50 publications
6
81
2
1
Order By: Relevance
“…The negative effects of apoptosis on fertilization and pregnancy are less present or even absent. Another explanation for the absence of predictive power of DNA damage for IVF/ICSI outcomes might be that when using DGC, which reduces the percentage of sperm with DNA denaturation, there exist other types of DNA damage that are not detected by acridine orange [8], but additionally affecting IVF/ICSI outcomes. As a consequence, sperm DNA integrity may or may not have an impact on the clinical results of IVF and ICSI cycles [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effects of apoptosis on fertilization and pregnancy are less present or even absent. Another explanation for the absence of predictive power of DNA damage for IVF/ICSI outcomes might be that when using DGC, which reduces the percentage of sperm with DNA denaturation, there exist other types of DNA damage that are not detected by acridine orange [8], but additionally affecting IVF/ICSI outcomes. As a consequence, sperm DNA integrity may or may not have an impact on the clinical results of IVF and ICSI cycles [12].…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, it might provide additional information regarding the outcome of in vitro fertilization [6,14,26,46]. However, there are authors denying this property to DNA damage [8,12,48].…”
Section: Introductionmentioning
confidence: 99%
“…This is very important if a DNA integrity test will be included in the panel as DNA integrity testing has recently been challenged as not having clinical relevance when used to evaluate male infertility [59]. The need to reevaluate old test scores is best illustrated by how a reevaluation of the use of the SCSA DNA fragmentation index (DFI) scores has dramatically changed how the test results are used to direct patients to appropriate ART [16,17]. The SCSA is the only DNA integrity test with substantial scientific literature supporting the credibility of this test for use in diagnosing male infertility, and up until 2007, patients whose sperm had a DNA fragmentation index (DFI)≥30 were told that their sperm had minimal to no chance for successful ART attempts at pregnancy [22,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for what many interpreted to be a loss of the SCSA's utility to predict ART outcome was not understood until the SCSA was evaluated for utility in predicting live birth outcome in each of the commonly used ART treatments, analyzing IUI, IVF, and ICSI live birth outcome as separate data sets. When this was done, it was found that the DFI significantly predicted live birth outcome in IUI cycles, but had no utility in predicting IVF or ICSI live birth outcome [16]. At present, the suggested course of treatment for patients with abnormal SCSA scores is that they be directed to ICSI, as this procedure has a higher live birth outcome rate than IVF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation